ANALISIS PERAN TEKNOLOGI BLOCKCHAIN DALAM MENINGKATKAN TRANSPARASI DAN EFISIENSI ASURANSI SYARIAH - Eni, Syahraeni; Buhari, Ulfah Luthfiyah; Amir, Muh. Fakhri; Kamiruddin, Kamiruddin (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The Islamic insurance industry has rapidly developed in recent decades, driven by Sharia principles such as risk sharing, justice, and avoidance of gharar (uncertainty) and riba (interest). This research aims to explore the role of blockchain technology in enhancing operations and risk management in the Islamic insurance industry. The research method used is a literature review, gathering data from books, journals, and articles related to blockchain technology and Islamic insurance. The findings indicate that blockchain technology has significant potential to improve transparency, security, and efficiency in Islamic insurance. Blockchain can record transactions openly and immutably, ensuring honesty and openness in line with Sharia principles. The use of smart contracts allows for the automation of claims processes and reduction of administrative costs. However, blockchain implementation faces challenges such as regulatory uncertainty, high initial costs, and a shortage of experienced professionals. The application of blockchain technology in Islamic insurance in Indonesia is still under development, with many Islamic insurance companies in the evaluation and trial phase before deciding on full adoption. This is due to the need for significant investment in technology infrastructure and limited understanding and expertise in blockchain technology among Islamic insurance practitioners.